Kajian Fenomena Penggunaan Bahasa Indonesia Campur Bahasa Inggris Dalam Pandangan Postmodern (Pengamatan Bahasa Pada Lirik Lagu Pop) - fawwaz, renaldy fahmi zakky; Siagian, Irwan (Peneliti.net, 2023)
The rapid advancement of modern technology has an impact on changes in all aspects of human life. The most important thing about this is culture. The existence of modern culture that has entered to change the cultural identity of Indonesia. There is a lot of mixing of cultures in this global world. Collaborative cultures are difficult to distinguish from indigenous cultures. Emergence of culture is often difficult to understand and so shocking. The most important thing in culture is finding a language. Lots of use of Indonesian mixed with English. The use of Indonesian mixed with English can be easily identified through the lyrics of a song. Song can be interpreted as a cultural product or a tool to communicate. Through language, they can see and describe the social changes that occur in society. The use of Indonesian mixed with English is very interesting to see a study because it can see the situation of socio-cultural cycles in today’s society. The postmodern critical cultural studies approach with the discourse analysis method is used to uncover the ideology, background and motives of using Indonesian mixed with English in the lyrics of a song. This research can be studied about the struggle of Indonesian culture with modern culture. Hegemony and symbolic domination are a danger and a latent threat to harmony in diverse cultures.